Porous nitrogen rich cadmium-tetrazolate based metal organic framework (MOF) for H-2 and CO2 uptake - Pachfule, Pradip; Banerjee, Rahul (Crystal Growth & Design, 2011)
The highly porous nitrogen rich metal organic framework [Cd-3(4-TP)(6)] (Cd-4TP-1) was synthesized solvothermally from the predesigned organic building block 4-tetrazole pyridine (4-TP) and Cd(II) as metal center using DMF as solvent. Cd-4TP-1 has a three-dimensional porous architecture where all the binding sites of Cd(II) are exclusively occupied by the nitrogen atoms from the mu(2)-tetrazolyl group or the pyridyl functionality of the 4-TP ligands. Cd-4TP-1 has Brunauer-Emmett-Teller (BET) and Langmuir surface areas of 472.2 and 728.6 m(2)/g, respectively, and shows 1.1 wt % H-2 (77 K) and 2.7 mmol/g CO2 uptake (273 K).

Porous carbons from nonporous MOFs: influence of ligand characteristics on intrinsic properties of end carbon - Aiyappa, Harshitha Barike; Pachfule, Pradip; Banerjee, Rahul; Kurungot, Sreekumar (Crystal Growth & Design, 2013)
Synthesis of porous carbons on direct carbonization of nonporous Zn-based MOFs has been achieved without using any additional carbon precursor. The effect of ligand nature on the resulting carbon porosity has been studied systematically using the MOFs synthesized from rigid and flexible ligands. The linear relations between Zn/C ratio of the MOF versus surface area of the resulting carbon, micro-porosity versus H-2 uptake achieved in these carbons, and surface area versus specific capacitance of the end carbons have been verified from the gas adsorption, molecular composition, and electrochemical studies, respectively. Cyclic voltammetry and charge-discharge cycling have been carried out to study the capacitive behavior of the carbons. The interdependence of capacitive behavior on the surface area has been analyzed using data derived from N-2 adsorption isotherms and charge-discharge curves. Among the carbons synthesized, C-MOF-2 shows maximal surface area of 1378 m(2)/g with a specific capacitance of 170 F/g at 1 A/g.

Porous-organic-framework-templated nitrogen-rich porous carbon as a more proficient electrocatalyst than Pt/C for the electrochemical reduction of oxygen - Pachfule, Pradip; Dhavale, Vishal M.; Kandambeth, Sharath; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Porous nitrogen-rich carbon (POF-C-1000) that was synthesized by using a porous organic framework (POF) as a self-sacrificing host template in a nanocasting process possessed a high degree of graphitization in an ordered structural arrangement with large domains and well-ordered arrays of carbon sheets. POF-C-1000 exhibits favorable electrocatalytic activity for the oxygen-reduction reaction (ORR) with a clear positive shift of about 40 mV in the onset potential compared to that of a traditional, commercially available Pt/C catalyst. In addition, irrespective of its moderate surface area (785 m2?g-1), POF-C-1000 showed a reasonable H2 adsorption of 1.6 wt?% (77 K) and a CO2 uptake of 3.5 mmol?g-1 (273 K).
Keywords: Adsorption; Electrochemistry; fuel cells; oxygen-reduction reaction; porous organic frameworks

Predesigned metal-anchored building block for in situ generation of Pd nanoparticles in porous covalent organic framework: application in heterogeneous tandem catalysis - Bhadra, Mohitosh; Sasmal, Himadri Sekhar; Basu, Arghya; Midya, Siba P.; Kandambeth, Sharath; Pachfule, Pradip; Balaraman, Ekambaram; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2017)
The development of nanoparticle-polymer-hybrid-based heterogeneous catalysts with high reactivity and good recyclability is highly desired for their applications in the chemical and pharmaceutical industries: Herein, we have developed a novel synthetic strategy by choosing a predesigned metal-anchored building block for in situ generation of metal (Pd) nanoparticles in the stable, porous, and crystalline covalent organic framework (COF), without using conventional reducing agents. In situ generation of Pd nanoparticles in the COF Skeleton is explicitly confirmed' from PXRD, XPS, TEM images, and N-15 NMR spectral analysis. This hybrid material is found to be an excellent reusable heterogeneous catalyst for the synthesis of biologically and pharmaceutically important 2-substituted benzofurans from 2-bromophencils and terminal alkynes via a tandem process with the turnover number up to 1101. The heterogeneity of the catalytic process is unambiguously verified by a mercury poisoning experiment and leaching test. This hybrid material shows superior catalytic performance compared to commercially available homogeneous as well as heterogeneous Pd catalysts.

Porosity prediction through hydrogen bonding in covalent organic frameworks - Karak, Suvendu; Kumar, Sushil; Pachfule, Pradip; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Easy and bulk-scale syntheses of two-dimensional (2D) covalent organic frameworks (COFs) represent an enduring challenge in material science. Concomitantly, the most critical aspect is to precisely control the porosity and crystallinity of these robust structures. Disparate complementary approaches such as solvothermal synthesis have emerged recently and are fueled in part by the usage of different modulators and acids that have enriched the COF library. Yet, the fundamental understanding of the integral processes of 2D COF assembly, induding their growth from nucleating sites and the origin of periodicity, is an intriguing chemical question that needs to be answered. To address these cardinal questions, a green and easy-to-perform approach of COF formation has been delineated involving acid-diamine salt precursors. The role of hydrogen bonding [d(av)(N-amine-H center dot center dot center dot O-acid); d(av) signifies the average N-amine-H center dot center dot center dot O-acid distances, i.e., the average distance from the H atom of the amine to the O atom of the acid] present in the acid-diamine salts in improving the COFs' crystallinity and porosity has further been decoded by thorough crystallographic analyses of the salt molecules. What is particularly noteworthy is that we have established the hydrogen-bonding distances d(av)(N-amine-H center dot center dot center dot O-acid) in the acid-diamine salts that are pivotal in maintaining the reversibility of the reaction, which mainly facilitates highly crystalline and porous COF formation. Moreover, this reactant-structure to the product-quality relationship has further been utilized for the synthesis of highly crystalline and porous COFs that are unattainable by other synthetic means.